Electoral competition, political parties and clientelism: evidence from local elections in South Africa. Issue 3 (3rd April 2023) - Dawson, Stephen; Charron, Nicholas; Justesen, Mogens Kamp
ABSTRACT: How does electoral competition shape parties' use of clientelist strategies during elections? In this article, we present a theoretical framework which suggests that in contexts where electoral clientelism is present but not ubiquitous, clientelist strategies take a distinctive form by being more considered and rationally targeted at individuals and areas that maximize the value of the transaction for the clientelist party. Using individual-level survey data collected in the aftermath of the South African municipal elections of 2016, we find considerable evidence to suggest that electoral competition moderates the relationship between several individual and municipal level variables and individuals' exposure to clientelist campaigns. Our results also demonstrate how the subtleties of targeting strategies differ between dominant and opposition parties depending on the level of competitiveness. These findings suggest the presence of a rational political economy of clientelism where parties carefully tailor their clientelist strategies to suit the local context.